(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2025)
From the late 19th century to the early 20th century, under the invasion and rule of French colonialism as well as the weakness of the feudal court, Vietnam fell into a state of tumult and darkness; the people’s lives were miserable and desperate. Faced with this situation, several great revolutionaries having patriotic spirit emerged, putting forward many progressive reformist ideas to save the country and help the people. One of the great and outstanding thinkers in this reformist movement was Phan Chau Trinh. Within the scope of this article, the author presents some of Phan Chau Trinh’s reformist thoughts, and analyzes some of the main factors that influenced the formation of his reformist thoughts. The article uses the research method of the dialectical materialist and historical materialist standpoint, considering Phan Chau Trinh’s writings and the related materials of contemporary activists. The article shows that the reformist thoughts of the patriot Phan Chau Trinh originated from his revolutionary spirit and love for his compatriots and shows his awareness of accepting new and progressive thoughts; through that, Phan Chau Trinh’s thoughts made significant contributions to the cause of national liberation of Vietnam, especially reflected in the inheritance by Nguyen Ai Quoc.